(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a bibliographical study of literature published on women in Madhya Pradesh after 1995. A systematic review of scholarly articles, books, reports, and other publications was conducted focusing on the status and experiences of women in various spheres including education, economy, health, politics, and society in general. Over 150 sources were reviewed and analyzed to provide a comprehensive overview of the research landscape on this topic. The time period from 1995 onwards was chosen to capture literature in the post-liberalization period which has seen major social and economic changes in India. Key findings show that while progress has been made towards women’s advancement, significant gaps persist in literacy, workforce participation, maternal health, gender violence, and political representation. Patriarchy and deep-rooted gender biases continue to hinder equality and empowerment. Recent government schemes and interventions are also examined for their impact. The study provides directions for future research for scholarship to support evidence-based policymaking and social change towards gender justice